Pengaruh Harga, Suasana Toko dan Kualitas Pelayanan terhadap Keputusan Pembelian di Waroenk Andya - Rafli Muhammad Firdaus; Misti Hirasih; Satrio Sudarso (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of price, store atmosphere, and service quality on consumer purchasing decisions at Waroenk Andya, Sidoarjo. A quantitative approach was used, employing a Non-Probability Sampling method with a purposive sampling technique involving 96 respondents. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression with SPSS version 25. The results indicate that all three independent variables significantly influence purchasing decisions, both partially and simultaneously. Among them, price is found to have the most dominant influence on purchasing decisions.